المقطع وتكوينة فى اللغات العربية والانجليزية والهوسا : دراسة وصفية صوتية تقابلية - يوسف، مصطفى محمد (جامعة إفريقيا العالمية - مركز البحوث والدراسات الإفريقية, 2018)
Syllable has no doubt played a vital role in human languages in terms of explaining the phonetics distinctions and paves the way towards good pronunciation and construction of sentences. This paper attempts to identify the area of similarities and dissimilarities between these English, Arabic and Hausa languages in syllable formation. The significance of this research stems from its intensive discussion of an important phenomenon among African Languages. It also helps researchers to advance their understanding in using syllable in these languages. The descriptive method is used in conducting this research. Thus, the paper discovers that there are many similarities between these languages in syllable formation, and the areas of differences are less prominent. Hence, the paper recommends that more effort should be invested in carrying out similar researches in this area
لا شك في أن المقاطع تؤدي دورا مهما في بيان الخصائص الصوتية للغة ما، وفي بيان سنن أهلها في التلفظ بها عن حاجاتهم المادية والمعنوية. وهذا المقال يرصد مواضع التشابه والاختلاف بين اللغات العربية، الإنجليزية والهوسا في النظام المقطعي، وتكتسب هذه الدراسة أهميتها من أنها تتناول ظاهرة مهمة في اللغات الأكثر تداولا في القارة الإفريقية. وكما تعين دراسي هذه اللغات على توسعة الآفاق العلمية في إدراك حقيقة هذه الظاهرة. واعتمد الباحث على المنهج الوصفي، حيث يدرس المقطع في اللغة العربية أولا، واللغة الإنجليزية ثانيا، واللغة الهوسوية ثالثا، ثم يعقد المقابلة بين هذه اللغات في هذه الظاهرة لمعرفة التشابه والاختلاف. وتوصلت الدراسة إلى أن هناك تشابها كبيرا بين هذه اللغات في النظام المقطعي، ومواضع الاختلاف فيها قليلة. وتوصي بتقديم المزيد من الدراسات التقابلية بين اللغات الإفريقية المختلفة في القضايا الصوتية.
Keywords: اللغة العربية -- اللغة الانجليزية -- لغة الهوسا -- الدلالات اللفظية -- اللسانيات الصوتية